Resistive wall mode stability and resonant field amplification in MAST high beta plasma. (30th September 2021) - Liu, Yueqiang; Kirk, A.; Keeling, D.L.; Kogan, L.; Du, X.D.; Li, L.; Piron, L.; Ryan, D.A.; Turnbull, A.D.
Abstract: The n = 1 ( n is the toroidal mode number) resistive wall mode (RWM) instability and the resonant field amplification (RFA) due to a stable RWM response are numerically investigated for an MAST high-pressure plasma scenario, utilizing the MARS-F Liu et al (2000 Phys. Plasmas 7 3681) and MARS-K Liu et al (2008 Phys. Plasmas 15 112503) codes, for the purpose of understanding the potential RWM behavior in MAST-U plasmas. Ideal kink stability analysis identifies a target plasma, with parameters similar to that of the reference equilibrium reconstructed from an MAST high-pressure discharge, that accesses the RWM regime. The unstable n = 1 RWM for the target equilibrium is subject to strong damping by the plasma toroidal flow and/or the drift kinetic effects from thermal particles. As a result, the mode is found to be stable under the experimental flow conditions, or even without flow stabilization if drift kinetic stabilization is included. The stability prediction is robust against variation of the assumed resistive wall minor radius. Active magneto-hydrodynamic (MHD) spectroscopy modeling, using the magnetic coils designed for controlling the edge localized modes (ELMs) in MAST-U as the antenna, shows strong RFA due to a stable RWM response in the target plasma. Maximal amplification, of 6–7 times larger than the applied vacuum field within the plasma, is obtained assuming a coil phasing of 120–180 degrees between the upper and lower rows of the ELM control coils. The MHD-kinetic hybrid model predicts generally higher RFA than the fluid model, in particular near the low-field and high-field sides of the plasma boundary surface. The MARS-F/K modeling thus shows that the RWM in MAST-U is subject to strong flow and kinetic stabilization, but can nevertheless be detected by active MHD spectroscopy.